Delayed administration of dopaminergic drugs is not associated with prolonged length of stay of hospitalized patients with Parkinson's disease. (February 2017) - Skelly, Rob; Brown, Lisa; Fogarty, Andrew
Abstract: Background: Punctual delivery of dopaminergic medication to Parkinson's disease (PD) patients may be important in optimizing disease control. We tested the hypothesis that prompt delivery ofl -dopa medications to emergency hospital inpatients was associated with a decreased length of stay in hospital. Methods: The study population consisted of all urgent hospitalizations for patients with a diagnosis of PD to the Royal Derby Hospital over a two-year period. Data were extracted on timing of delivery of drugs, number of co-morbidities and length of stay. Statistical analysis used linear regression adjusting for within admission clustering. Results: 431 individuals provided data from a total of 737 admissions. 39% of scheduledl -dopa doses were either not given or administered over 30 min later than the scheduled time. There was no association between the omission or timing of a dose of PD medication and length of stay in hospital. The number of coded diagnoses was strongly associated with length of stay with a dose-response association (pTREND <0.001). Those with 10 concurrent diagnoses had a 11 day longer stay (95% confidence intervals: +2 to +21) than those with no comorbidities. Conclusions: Delayed administration of dopaminergic drugs is not associated with prolonged length of stay of in patients with PD who were admitted to hospital as an emergency. However, the number of co-existing medical diagnoses was associated with length of stay, and early attention to these has the potential to improve patient care and decrease length of stay in hospital. Highlights: The study population was 737 emergency admissions of PD patients. 39% ofl -dopa doses were omitted or delayed more than 30 min. Delays tol -dopa administration in hospital do not prolong length of stay. The number of co-morbidities is positively correlated with length of stay. Weekends do not affect delays to dopaminergic medication administration.